2018
DOI: 10.5194/acp-18-5467-2018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of organic nitrate constituents of secondary organic aerosol (SOA) from nitrate-radical-initiated oxidation of limonene using high-resolution chemical ionization mass spectrometry

Abstract: Abstract. The gas-phase nitrate radical (NO q 3 ) initiated oxidation of limonene can produce organic nitrate species with varying physical properties. Low-volatility products can contribute to secondary organic aerosol (SOA) formation and organic nitrates may serve as a NO x reservoir, which could be especially important in regions with high biogenic emissions. This work presents the measurement results from flow reactor studies on the reaction of NO q 3 with limonene using a High-Resolution Time-of-Flight Ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 87 publications
6
66
0
Order By: Relevance
“…Another major series of compounds in the spectra is found for C 10 H 15 O x N, which can be observed at m/z 268.08 (C 10 H 15 O 6 N), 284.07 (C 10 H 15 O 7 N), 300.07 (C 10 H 15 O 8 N), and 316.06 (C 10 H 15 O 9 N) and contribute 1.6 %, 1.5 %, 1.8 %, and 1.5 %, respectively, to the profile signal, resulting in the highest contributions compared to all the other factors except for C 10 H 15 O 7 N and C 10 H 15 O 8 N, which contribute ∼ 1.3 % and ∼ 1.7 % to the NightSOA2 EESI profile signal (ag s −1 ). These species are consistent with NO 3 oxidation products of atmospherically relevant monoterpenes such as limonene (Faxon et al, 2018).…”
Section: Secondary Night-time Factorssupporting
confidence: 76%
“…Another major series of compounds in the spectra is found for C 10 H 15 O x N, which can be observed at m/z 268.08 (C 10 H 15 O 6 N), 284.07 (C 10 H 15 O 7 N), 300.07 (C 10 H 15 O 8 N), and 316.06 (C 10 H 15 O 9 N) and contribute 1.6 %, 1.5 %, 1.8 %, and 1.5 %, respectively, to the profile signal, resulting in the highest contributions compared to all the other factors except for C 10 H 15 O 7 N and C 10 H 15 O 8 N, which contribute ∼ 1.3 % and ∼ 1.7 % to the NightSOA2 EESI profile signal (ag s −1 ). These species are consistent with NO 3 oxidation products of atmospherically relevant monoterpenes such as limonene (Faxon et al, 2018).…”
Section: Secondary Night-time Factorssupporting
confidence: 76%
“…The chemical mechanism used in Browne et al (2013) and Zare et al (2018) are based on the Master Chemical Mechanism (MCM) that is well known in the degradation chemistry of VOC in the gas phase (Jenkin et al, 1997;Saunders et al, 2003). However, the same mechanism performs poorly in regards to the chemical composition of SOA (Faxon et al, 2018) as well as the prediction of SOA formation (Ruggeri et al, 2016;Boyd et al, 2017) when equipped with gasparticle partitioning modules based on the absorptive gas-particle partitioning theory (Pankow, 1994). It is, therefore, reasonable to argue that the chemical composition of pON could greatly differ from that of total ON predicted by the MCM.…”
Section: Hydrolyzable Fraction Of Particulate Organic Nitratementioning
confidence: 99%
“…The most abundant pON species in NGT-ONRich were C 5 H 9 NO 7 and 10 C 10 H 15 NO 8 , accounting for 7.8 and 3.5 % of pON signals in this factor, respectively. C 10 H 15 NO 8 has been characterized in multiple chamber studies as major products of α-/β-pinene/limonene+NO 3 ⋅ and α-/β-pinene photooxidation with the presence of NO x (Nah et al, 2016;Lee et al, 2016;Faxon et al, 2018;Takeuchi and Ng, 2019). At Yorkville, the majority of C 10 H 15 NO 8 was presented in NGT-ONRich, implying that nocturnal chemistry is its most important source.…”
Section: Figaero-cims Oa Factorsmentioning
confidence: 99%
“…The efficient nocturnal isoprene oxidation is possibly via the reaction with nitrate radicals rather than with ozone (Ng et al, 2008;Brown et al, 2009;Schwantes et al, 2015;Fry et al, 2018). In addition, the recent work by Fry et al (2018) suggested a substantially longer nighttime peroxy radical lifetime in 5 ambient air versus under chamber conditions, which allows for the formation of lower-volatility products and thus higher SOA yields from isoprene nocturnal chemistry.…”
Section: Tracer Species Detected By Figaero-cims and Their Implicationsmentioning
confidence: 99%